2013
DOI: 10.1038/ncomms3376
|View full text |Cite
|
Sign up to set email alerts
|

Single-mode tunable laser emission in the single-exciton regime from colloidal nanocrystals

Abstract: Whispering-gallery-mode resonators have been extensively used in conjunction with different materials for the development of a variety of photonic devices. Among the latter, hybrid structures, consisting of dielectric microspheres and colloidal core/shell semiconductor nanocrystals as gain media, have attracted interest for the development of microlasers and studies of cavity quantum electrodynamic effects. Here we demonstrate single-exciton, single-mode, spectrally tuned lasing from ensembles of optical anten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
135
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(136 citation statements)
references
References 58 publications
1
135
0
Order By: Relevance
“…by coating a silica microsphere with a ring of colloidal nanoparticles [68]. As a result, narrow laser lines as short as of 6 pm were obtained in the single and biexciton regimes with lasing thresholds of 68.5 μW and 123.3 μW, respectively.…”
Section: Lasingmentioning
confidence: 95%
“…by coating a silica microsphere with a ring of colloidal nanoparticles [68]. As a result, narrow laser lines as short as of 6 pm were obtained in the single and biexciton regimes with lasing thresholds of 68.5 μW and 123.3 μW, respectively.…”
Section: Lasingmentioning
confidence: 95%
“…shell structures [116,117], for which the so-called seeded-growth method developed by Manna and coworkers [118] led to an unprecedented control of size and shape. These nanostructures have been used, for example, in combination with silica microspheres on whispering-gallery-mode resonators to demonstrate single-mode, spectrally tunable lasing [119]. Achieving optical gain without using external resonators is however still a challenging task, due to the competing detrimental process of Auger recombination.…”
Section: Compound Semiconductors Type-i Vs Type-ii Structuresmentioning
confidence: 99%
“…13 With all of these aforementioned promises, in the nanocrystal lasing context, CdSe/CdS NRs have become one of the most heavily studied materials systems. 18,24 Recently, singlemode, single-exciton and tunable laser emission on a silica microsphere 25 and low-threshold amplied spontaneous emission (ASE) and lasing with two-photon pumping mechanism 10 have been successfully demonstrated with CdSe/CdS core/shell NRs. Moreover, it was shown that nearly temperature-independent ASE can be possible with CdSe/CdS core/shell NRs 26 and controllable transition of the ASE peak from the CdSe core region to the CdS shell region can be nely tuned by changing the length of the nanorod and the excitation intensity.…”
mentioning
confidence: 99%